Prognostic impact of aborted cardiac arrest in patients with acute myocardial infarction. (3rd October 2022) - Presume, J; Gomes, D; Strong, C; Tralhao, A; Aguiar, C; Trabulo, M; Almeida, M; Ferreira, J; Mendes, M
Abstract: Background: Aborted cardiac arrest (ACA) during the acute ischaemic phase is a relatively frequent but often undervalued complication of acute myocardial infarction (AMI). The aim of this study was to evaluate the clinical and prognostic impact of aborted cardiac arrest in AMI patients and investigate its correlation with infarct size. Methods: We conducted a single-centre retrospective study enrolling consecutive patients admitted for AMI, from January 2016 to December 2018. ACA was defined as the need for advanced life support measures and defibrillation, either out-of-hospital or in-hospital, up until culprit vessel revascularisation. Infarct size was estimated using peak serum troponin T, impact on left ventricular ejection fraction (LVEF ≤50%) and echocardiographic wall motion index (WMI). Clinical outcomes included cardiogenic shock (SCAI C or more), need for mechanical circulatory support (MCS), major bleeding events (BARC ≥3) during in-hospital phase and all-cause mortality during follow-up. Results: A total of 571 patients were included (65±13 years old, 72% male). Overall, 237 had anterior STEMI, 39 patients (6, 8%) suffered ACA (21 out of hospital), 60 progressed into cardiogenic shock throughout the hospitalisation, 7 needed MCS, and 52 had BARC ≥3 bleeding. During a mean follow-up of 32 months, 96 patients died. ACA was significantly associated with higher peak serum troponin T (4802 [1950; 9420] vs 2659 [555; 6708] ng/L – p=0.004), higher proportion of patients with reduced or mildly reduced LVEF (60% vs. 36.5%, p=0.018) and higher WMI (1.7 [1.4; 2.3] vs. 1.5 [1.2; 1.8], p=0.016). Moreover, ACA was also associated with higher risk of cardiogenic shock occurrence (64.1% vs. 6.6%, p<0.001 – OR 25.357 (12.115–53.073)), higher need for MCS (7.9% vs 0.8%, p<0.001 – OR 11.271 (2.427–52.343)) and higher incidence of BARC ≥3 bleeding events (28.2% vs. 8.4%, p<0.001 – OR 4.705 (2.185–10.128)) – Table 1. On univariate Cox regression, ACA showed significant association with all cause death, which remained highly significant after multivariable adjustment (OR 2.431 (1.181; 5.002); p=0.016). Conclusion: The occurrence of aborted cardiac arrest in patients with AMI was associated with increased morbidity and mortality. This may be driven by a larger area of arrhythmia prone ischemic myocardium. Funding Acknowledgement: Type of funding sources: None.